Effect of different incubation period on microbial biomass carbon (C) level in two soil series - Che Jamil, Mohd Nizar (2015)
A study on effect of different incubation period on the level of microbial biomass carbon (C) in two soil series was carried out in open-land at Putrajaya (Prang Series) and University Agriculture Park (TPU), Puchong, Selangor (Serdang Series). Serdang soil series was taken at Universiti Agriculture Park while Prang series was taken at Putrajaya. 100 m2 plot was established at each site where about 10 soil samples were collected at the depth of 0-20 cm depth to a form a composite sample. Five replicates were made out of the composite sample for each plot. The physical and chemical properties analyzed in this study include soil texture, bulk density, soil acidity (pH), electrical conductivity (EC) and soil organic carbon (SOC). The fresh soil samples were kept chilled in chiller at 4°C prior for analysis of microbial biomass carbon (C). Both soil series exhibit clay soil texture, where Serdang series soil has slightly higher amount of sand fraction and lower amount of clay compared to Prang series soil. Higher moisture and organic carbon also act as predisposing factor that enhances higher growth of microbial biomass C in Serdang soil. The Serdang soil series soil samples can be subjected to dichromate digestion after 1st or 2nd day of incubation. In contrast, Prang series required a period of 2 days or 4 days to ideal amount of microbial biomass C prior for dichromate digestion. Further investigation on wider number of soil series need to be carried out. The results obtained would be beneficial in modifying the chloroform fumigation extraction and incubation timing as it can helps in reducing the amount of time taken.